Cost-effectiveness and budget impact analysis of viscosupplementation with hylan G-F 20 for knee and hip osteoarthritis - Migliore A; Integlia D; Pompilio G; Di Giuseppe F; Aru C; Brown T (Dove Medical Press, 2019)
Alberto Migliore,1 Davide Integlia,2 Giuseppe Pompilio,2 Francesca Di Giuseppe,2 Cinzia Aru,2 Tray Brown31Unit of Rheumatology, San Pietro Fatebenefratelli Hospital, Rome, Italy; 2ISHEO Srl, Rome, Italy; 3Department of Public Health and Primary Care, University of Cambridge, Cambridge, UKPurpose: To estimate the cost-effectiveness and budget impact of viscosupplementation with one intra-articular (IA) injection of 6 mL hylan G-F 20 (Synvisc-One®,) and with three injections of 2 mL hylan G-F 20 (Synvisc®,3×2) in knee osteoarthritis (OA) patients compared with conventional support therapy (CST – eg, NSAIDs and acetaminophen) and the cost-effectiveness of one IA injection of 2 mL hylan G-F 20 (Synvisc®,1×2) in hip OA patients compared with CST from an Italian Health System perspective.Methods: The model used was a Markov model with states for stages II–IV on the Kellgren–Lawrence scale and runs on 6-month cycles over a 5-year time horizon. A 3.5% discount was applied to both costs and utilities. Direct costs were determined from the perspective of the Italian National Health Service. A one-way and probabilistic sensitivity analysis was conducted for both comparisons.Results: Hylan G-F 20 1×6 mL and hylan G-F 20 3×2 mL for knee OA were very likely to be cost-effective when compared to acetaminophen (ICER = €3,160.61 and €3,845.81 per QALY, respectively) and NSAIDs as both ICERs are below €25,000. The hip OA treatment by hylan G-F 20 1×2 mL was dominant compared to NSAIDs and very likely compared to acetaminophen. The results of the cost-effectiveness analysis were confirmed by one-way sensitivity analysis. The budget impact analysis for knee and hip OA showed a small increase in expenditure during 5 years.Conclusions: Hylan G-F 20 1×6 mL/hylan G-F 20 is a cost-effectiveness treatment compared to NSAIDs and acetaminophen in the treatment of knee/hip OA in Italy. The treatment of hip and knee OA resulted in cost-saving with hylan G-F 20 1×2 mL and economically sustainable with hylan G-F 20 1×6 mL. However, Real Word Evidence studies should be conducted in order to estimate costs associated with both prosthetics and to understand the reduction of physiotherapy and medication due to hylan G-F 20.Keywords: budget impact, cost-effectiveness, osteoarthritis, viscosupplementation, hylan G-F 20, total knee or hip replacement